Dynamic Weight-bearing Magnetic Resonance in the Clinical Diagnosis of Internal Temporomandibular Joint Disorders - Giannini, Silvana; Chiogna, Giorgio; Balzano, Rosario Francesco; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2019)
Temporomandibular joint (TMJ) disorders can be painful and cause functional limitations and bone changes. Deeper clinical knowledge of the pathologies related to the TMJ has always been hindered by the difficult identification of the causes that limit its movement. Weight-bearing magnetic resonance imaging (WBMRI) can reproduce the articular movement in orthostasis and allows the evaluation of joint movement. WBMRI, compared with other procedures such as double-type condylography and real-time dynamic ultrasound, helps to better identify tissue characteristics of the articular glenoid-condylar surfaces, articular space, disk position on both the open and closed mouth, and the locoregional musculotendinous area. WBMRI also identifies the true position of the articular disk in orthostasis, emphasizing the different joint positions compared with the study carried out in a clinostatic (supine) position.
Keywords: temporomandibular joint; weight-bearing MRI; functional weight-bearing examination